2021
DOI: 10.3390/su14010280
|View full text |Cite
|
Sign up to set email alerts
|

Determining Factors Affecting Customer Intention to Use Rooftop Solar Photovoltaics in Indonesia

Abstract: Many developing countries on the equator, including Indonesia, have the potential for renewable and sustainable resources, such as solar energy. However, despite the enormous potential, the adoption level remains low. Previously, several studies discussed the potential, the feasibility, and the supporting policy of this technology, but none have been discussed from the customers’ perspective on a national scale. Therefore, this study attempts to determine the factors affecting the customers’ intention to use s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 35 publications
(62 reference statements)
4
16
0
Order By: Relevance
“…In addition, it is recommended to use the UTAUT2 together with an external model to improve the explanatory power (Tamilmani et al, 2017), which led us to our model that integrates the TPB and the UTAUT2. Previous studies have successfully combined these two models to identify the factors in uencing behavioral intentions to adopt technology (Bai, 2020;Bekti et al, 2022;Yuen et al, 2020). Therefore, we posit that integrating these two models allows us to accurately understand science teachers' intentions to use AR.…”
Section: Previous Workmentioning
confidence: 96%
“…In addition, it is recommended to use the UTAUT2 together with an external model to improve the explanatory power (Tamilmani et al, 2017), which led us to our model that integrates the TPB and the UTAUT2. Previous studies have successfully combined these two models to identify the factors in uencing behavioral intentions to adopt technology (Bai, 2020;Bekti et al, 2022;Yuen et al, 2020). Therefore, we posit that integrating these two models allows us to accurately understand science teachers' intentions to use AR.…”
Section: Previous Workmentioning
confidence: 96%
“…The users' ability to try out an innovation will improve the simplicity and chances of adopting that particular innovation (Lin and Chen, 2012). Simplicity positively and significantly impacts customers' attitudes toward RSPV systems (Bekti et al, 2022). Rogers (2003) defined trialability as "the extent to which people can experience the innovation before actual use".…”
Section: Rooftop Solar Photovoltaic Systems In Indiamentioning
confidence: 99%
“…Recently, environment-friendly technological innovative products have been largely adopted by customers in domestic as well international markets (Ahmed et al, 2022). Numerous studies reveal customer attitude in the framework of adoption intentions toward solar energy (Yazdanpanah et al, 2015;Sun et al, 2020;Alam and Fathima, 2022;Bekti et al, 2022;Ahmed et al, 2022;Fathima et al, 2022), subjective norms (Masrahi et al, 2021;Alam and Fathima, 2022) and perceived behavior control (Yazdanpanah et al, 2015;Masrahi et al, 2021;Fathima et al, 2022) have a positive and significant impact on their behavioral intention to adopt rooftop solar PV systems as the source of renewable energy. In the context of Zambia and Pakistan, Zulu et al (2021) and Waris et al (2022) revealed that households' attitude, subjective norms and perceived behavioral control significantly impact their intention toward the adoption of solar energy at a small scale.…”
Section: Rooftop Solar Photovoltaic Systems In Indiamentioning
confidence: 99%
See 1 more Smart Citation
“…In 2019, approximately 42,000, 55,430, and 255,870 ktonnes of fruits, vegetables [53], and cereals [54], respectively, were produced in Europe with conventional farming [55,56]. It should be mentioned that non-edible parts of these agricultural products and rapeseed can be used for the production of biofuels [57,58] depending on the availability of money and consumers' habits [59]. Tables 2 and 3 show minimum and maximum benefits in human health per person and ecosystems quality (terrestrial), respectively, if fungicides are eliminated in fruits, vegetables, and cereals and rapeseed production in Europe.…”
Section: Endpoint Impacts Due To Fungicides Applicationmentioning
confidence: 99%